Analysis of Musyarakah and its Implementation at BMT Fadhilah Sentosa Bekonang - Aulia Azka Maulana; Muthoifin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The mutual cooperation between the customer and the capital owner, namely Baitul Maal Wat Tamwil or BMT, is a partnership allowed by Allah SWT as long as there is no oppression towards either party in the partnership.